A framework for modelling customer invoice payment predictions - Moore, Willem Roux (Stellenbosch : Stellenbosch University, 2025)
Moore, W. R. 2025. A framework for modelling customer invoice payment predictions. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/42773281-13ed-452b-9d09-1cfebefc123a